Cryptographically Generated Addresses (CGAs): A survey and an analysis of performance for use in mobile environment - Qadir, Sana; Siddiqi, Mohammad Umar (IJCSNS, 2011)
CGAs are cryptographically generated IPv6 addresses and are one of the most novel features introduced in IPv6. They have the promising potential of being the basis of authentication mechanisms for Mobile IPv6 because they do not require hosts to share information or security infrastructure. A mobile environment however has several resource constraints that must be considered before any mechanism can be deemed feasible. This paper undertakes to survey all the work done on CGAs and their performance. The goal is to identify and discuss parameters that have an impact on performance (e.g. the public-key cryptosystem being used). This should help in proposing possible modifications and parameters to ease the adoption of CGAs in a mobile environment. As a starting point, the CGA generation and verification algorithms are implemented with the help of a cryptographic library designed especially for embedded systems. An evaluation of the performance of this implementation is undertaken and a comparison is made with the results reported in previous studies. Based on this, a recommendation is made for the parameters that should be used by mobile nodes when using CGAs. The longterm modification that has the most potential for improving the performance of CGAs in a resource-limited setup is also identified